1995
DOI: 10.1055/s-2007-979752
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Elevation in Specific Serum Enzymes for Subsequent Development of Hypoxic-Ischemic Encephalopathy or Intraventricular Hemorrhage in Full-Term and Premature Asphyxiated Newborns

Abstract: Serum lactate dehydrogenase (LDH), aspartate aminotransferase (ASAT), and hydroxybutyrate dehydrogenase (HBDH) activities are significantly elevated in asphyxiated newborns within the first days of life. The approach of the present study was to evaluate firstly if serum levels of these enzymes correlate with the development of hypoxic-ischemic encephalopathy (HIE) and periventricular-intraventricular hemorrhage (PIVH) in full-term and premature asphyxiated newborns, and secondly if postnatally elevated enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…This finding that both groups of premature infants, with and without BPD, show early enzyme increase after birth, as compared with the reference values of healthy, term newborns, corresponds to results of previous investigations, where postpartal enzyme elevations are the results of hypoxic-ischemic events, independently of birth weight and gestational age [8,[11][12][13][14]. According to Lackman's group [5][6][7][8], it is known that any secondary hypoxia, due to the development of acute or chronic pulmonary insufficiency, is insignificant in comparison with the primary, perinatal hypoxic-ischemic event. Possibly, interventions aimed at preventing pulmonary damage by reducing ventilatorand oxygen-induced injury or by modifying the resulting inflammatory process, may help to prevent and therefore attenuate the effects of unresolved acute lung disease associated to hypoxia.…”
Section: Discusssionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding that both groups of premature infants, with and without BPD, show early enzyme increase after birth, as compared with the reference values of healthy, term newborns, corresponds to results of previous investigations, where postpartal enzyme elevations are the results of hypoxic-ischemic events, independently of birth weight and gestational age [8,[11][12][13][14]. According to Lackman's group [5][6][7][8], it is known that any secondary hypoxia, due to the development of acute or chronic pulmonary insufficiency, is insignificant in comparison with the primary, perinatal hypoxic-ischemic event. Possibly, interventions aimed at preventing pulmonary damage by reducing ventilatorand oxygen-induced injury or by modifying the resulting inflammatory process, may help to prevent and therefore attenuate the effects of unresolved acute lung disease associated to hypoxia.…”
Section: Discusssionsupporting
confidence: 89%
“…In fact, no previous studies have defined distinct inclusion criteria for acute and chronic respiratory disorders, and performed enzyme measurements serially during and after the neonatal period. Recently, Lackman and co-workers [5][6][7][8] found that AST, LDH and HBDH measurements per-Zanardo/Rizzo/Trevisanuto/Simbi/Golin/ Magarotto/Marzari formed within the first 72 h of life were highly predictive for the development of hypoxia-related neurologic disorders, while they were not significantly altered by the development of RDS.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate prognosis in infants born Möller/Thielsen/Schaible/Reiss/Kohl/ Welp/Gortner with low umbilical pH or Apgar scores, the retrospective evaluation of the degree of organ hypoxia, after the instability during the first days, is important. Markers of organ hypoxia have been found to be significantly increased in asphyxiated infants, and a correlation with high levels of hypoxia markers of different organs and brain damage has been documented for CK and CK-MB [9,11,19], for alanine and aspartate aminotransferase [19,22], neuron-specific enolase [23,24], and creatinine levels [4,9,10]. Especially creatinine, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…0.05 was considered to be significant (Bonferoni correction). As 0.3 ng/ml troponin T has been shown to indicate myocardial hypoxia in adults [2,9,13,[19][20][21], we examined its positive predictive value in asphyxiated newborns. As it was 1.0 we than searched for the lowest level of troponin T still associated with a positive predictive value for the diagnosis of asphyxia of 1.0 to determine a possible cut-off level.…”
Section: Methodsmentioning
confidence: 99%